1987
DOI: 10.1111/j.1939-0025.1987.tb03572.x
|View full text |Cite
|
Sign up to set email alerts
|

Downward comparison and coping with serious medical problems.

Abstract: Correlates of selective comparisons by mothers of high-risk infants and individuals with rheumatoid arthritis showed that mothers were especially likely to make downward comparisons. Arthritis patients making downward comparisons were rated by their health care providers as more positively adjusted, independent of actual severity of illness. Implications for support providers are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
73
2
5

Year Published

1988
1988
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 113 publications
(85 citation statements)
references
References 17 publications
5
73
2
5
Order By: Relevance
“…For example, Wood, Taylor and Lichtman (1985) reported that most female breast cancer patients felt much better when downward comparing with other worse-off victims. The similar finding was evidenced in a considerable body of research about downward social comparison among populations facing a health threat and mentally handicapped, such as those with cancer (van der Zee, Agterberg, Peeters, Mooi & Schellekens, 1996), arthritis (Giorgino, Blaloc, Devellis, DeVellis, Keefe & Jordan, 1994), chronic pain (Affleck, Tennen, Pfeiffer, Fifield & Rowe, 1987;Tennen, McKee & Affleck, 2000) and stress (Gibbons & Boren, 1985). Embedded in this approach is the assumption that upward comparison is the opposite of downward comparison.…”
Section: Introductionsupporting
confidence: 60%
“…For example, Wood, Taylor and Lichtman (1985) reported that most female breast cancer patients felt much better when downward comparing with other worse-off victims. The similar finding was evidenced in a considerable body of research about downward social comparison among populations facing a health threat and mentally handicapped, such as those with cancer (van der Zee, Agterberg, Peeters, Mooi & Schellekens, 1996), arthritis (Giorgino, Blaloc, Devellis, DeVellis, Keefe & Jordan, 1994), chronic pain (Affleck, Tennen, Pfeiffer, Fifield & Rowe, 1987;Tennen, McKee & Affleck, 2000) and stress (Gibbons & Boren, 1985). Embedded in this approach is the assumption that upward comparison is the opposite of downward comparison.…”
Section: Introductionsupporting
confidence: 60%
“…La comparación temporal sólo ha sido evaluada en un estudio (Affleck et al, 2001) y en otros dos la comparación lateral (junto con la ascendente y la descendente) (Blalock et al, 1990;De Vellis et al, 1991). Algunos estudios se han centrado en ver los efectos de una única dirección: la descendente (Affleck et al, 1987;Affleck et al, 1988) o la ascendente (Neugebauer et al, 2003). La interpretación de identificación y contraste aparecen como variables única-mente en un estudio (Blalock et al, 1990), aunque en otro se hace referencia a ellas analizando si el paciente destaca las similitudes o las diferencias respecto de quién se compara (Heidrich, 1996).…”
Section: Revisión Del Constructo De Comparación Social Y Su Evaluaciónunclassified
“…A las personas de estos estudios se les indicaba que se comparasen con otra persona respecto a la percepción de síntomas, la gravedad de la enfermedad, el estado físico, el ajuste, el estado de salud y el funcionamiento social (Affleck et al, 1987;Affleck et al, 1988;Blalock et al, 1989;Blalock et al, 1990;Heidrich, 1996). Además se ha valorado los sentimientos asociados a dicha comparación independientemente de valorar posteriormente su estado emocional como resultado de adaptación (Heidrich, 1996 (Affleck et al, 1988); †: Escala de Comparación Social de Heidirch y Ryff (1993).…”
Section: Revisión Del Constructo De Comparación Social Y Su Evaluaciónunclassified
See 1 more Smart Citation
“…It is not yet possible to predict when disease flares of RA will occur, but the flares are often severely disabling and a source of further degeneration of tissue. The little research which has focused on the role of appraisal in arthritis has assessed appraisals of controllability (7) and predictability (8), and has indicated that these perceptions of control are correlated with psychological adjustment to RA.…”
Section: Definitions Of Copingmentioning
confidence: 99%